NEEDS ASSESSMENT: BASIS FOR TEACHERS TRAINING DESIGN - Salvador, Stephanie A (IDEAS: Journal of Management & Technology, 2024)
This study aimed to evaluate the training needs  of teachers    and propose a training design based on the gathered data from public elementary school teachers in the Province of Capiz.  Foreign and local literatures   related to training needs assessment were reviewed in relation to their relevance and implications of the study. When professionals are exposed to various realities of the communities and use their skills to address social issues they become more beneficial because professional development is a transformative space and dialogical for nurturing active and socially conscious professionals (Banderlipe, 2022). On the other hand, the study of Villaluz, G. et al, (2018) “A pathway to quality education is community engagement in teaching-learning” states that positive changes in the teaching profession in community engagement through observation, constant planning, and critical reflection is evident. This allows transformation of student performance, effective sharing of professional knowledge, sharing of strategies and reading of updated literature in teaching and learning in community engagement. Quantitative data from the 368 randomly selected respondents who answered the validated and reliability tested researcher-made questionnaire and qualitative data from ten FGD participants coming from the Schools Division of Capiz and Roxas City respectively using a mixed methods of research. Statistical tools used to analyse and interpret the data were frequency count, percentage and mean. Findings of the study revealed that training for teachers in the Province of Capiz is very much needed in terms of curriculum and planning, content knowledge and pedagogy, diversity of learners and learning development, community linkages and professional engagement, and personal growth and professional development. In terms of assessment and reporting was found moderately needed. These needs are similar for the teachers regardless of their socio-demographic profile such as age, sex, residence, highest educational attainment, and length of service. Based on the results of the study, a training design has been proposed focused on the identified areas namely: 21st Century Skills and ICT integration in Teaching; Utilization of Research-based in Teaching; and Teaching Leadership and Management. These recommendations were laid by the researcher to promote and support the pedagogical skills and professional development of teachers for better strategies in teaching and better learning outcomes through training design.